2023
DOI: 10.1186/s12910-023-00930-z
|View full text |Cite
|
Sign up to set email alerts
|

To donate or not to donate? Future healthcare professionals’ opinions on biobanking of human biological material for research purposes

Abstract: Background Over the last few decades biobanks have been recognised as institutions that may revolutionise biomedical research and the development of personalised medicine. Poland, however, still lacks clear regulations regarding the running of biobanks and the conducting of biomedical research. While the awareness of the general public regarding biobanks is low, healthcare professions and medical students also lack basic knowledge regarding biobanks, and such ignorance may affect their support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…A high level of acceptance of participation in biobanking and donation of their own HBM do not correspond with an equally high level of knowledge on biobanking. Polish research performed among students of different medical studies revealed deficits of knowledge on biobanking (Krajewska-Kułak et al, 2011), its specificity and role in modern medicine along with relatively high eagerness of donation of their own tissue to biobanks (Domaradzki et al, 2023). Similar results were obtained in the research carried out among future health and care professionals (HCPs) in Saudi Arabia (Merdad et al, 2017) and Egypt (Ziady et al, 2017;Abdelhafiz et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A high level of acceptance of participation in biobanking and donation of their own HBM do not correspond with an equally high level of knowledge on biobanking. Polish research performed among students of different medical studies revealed deficits of knowledge on biobanking (Krajewska-Kułak et al, 2011), its specificity and role in modern medicine along with relatively high eagerness of donation of their own tissue to biobanks (Domaradzki et al, 2023). Similar results were obtained in the research carried out among future health and care professionals (HCPs) in Saudi Arabia (Merdad et al, 2017) and Egypt (Ziady et al, 2017;Abdelhafiz et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
“…Although there are several studies on the attitudes of Polish citizens towards biobanking of human biological material (HBM) for research purposes (Majchrowska et al, 2022;Pawlikowski et al, 2022;Domaradzki et al, 2023;Pronicki et al, 2023), there remains a shortage of studies on the attitudes of (future) pharmacists on research biobanks. Thus, this study was designed to assess knowledge and attitudes of Polish pharmacy students on research biobanks.…”
Section: Methodsmentioning
confidence: 99%
“…In a 2019 survey in Latvia this percentage was 25.8% [6]. In Poland in 2023, around less than three quarters (71%) of medical students encountered the term biobank [37]. In 2013 in Poland, less than half (48%) of respondents associated a biobank with an institution related to medicine and 37% of respondents associated it with an institution related to scientific activities [38].…”
Section: Public Awareness Of Biobanks and The Scientific Research Dur...mentioning
confidence: 99%
“…The most of them declared that consent should be acquired before every new research project. Less than one third of respondents stated that no additional consent should be required if the donor consents while donating [37]. In 2023 in Poland, it was shown that 58.8% of respondents believe that they must give their consent to biobank their samples, 34.2% have no opinion on this and 7.0% believe that they do not have to give their consent to biobanking.…”
Section: The Approach To Informed Consentmentioning
confidence: 99%
“…This poses a problem as considerable effort and cost were invested in gathering and storing these samples. While broad consent permits secondary sample use in other contexts, participants typically favor specific consent over it [ 99 ]. Furthermore, participants usually interact solely with their study physician, remaining unaware of the biobank where their samples reside.…”
Section: Future Directions and Emerging Technologiesmentioning
confidence: 99%